On Martin Luther's Statement, "Fides Creatrix Divinitatis". (2nd September 2013) - Walter, Gregory
Abstract: Martin Luther's statement "faith creates divinity" depends upon the antecedent promise of the crucified and triune God. When considered as a theology of gift, this statement illustrates that faith makes divinity by giving God glory.